(untitled) (Academic Journal of International University of Erbil, 2025)
Establishing a strong financial market could help countries economically by acting as an accelerator. It has been discovered that countries with robust stock markets promote the creation of decent jobs, improve national income, and support economic expansion that is consistent with long-term economic growth. This study aimed to investigate the effect of financial market development on economic performance among the Asia-Pacific Economic Cooperation (APEC) countries. The data, which spans the prior 32 years from 1991 to 2022, has been collected from reputable databases, such as Internal Monetary Fund (IMF) and World Bank Data. The Fixed effect model with GLS cross-section weight was used to assess the above association. The findings display that FDI has a positive but insignificant influence on economic performance measured by (GNI and GDP). MAC has an adverse impact on GNI, but it has a beneficial impact on GDP, suggesting that although the stock market drives economic growth, its influence on national income is insignificant. Efficiency in the financial markets increases GDP but also increases disparities in income distribution, whereas depth in the financial markets increases GNI but reduces GDP growth. The results emphasize the necessity of balanced approaches to achieve equitable and sustained economic performance. To encourage economic growth, policymakers should give priority to fostering stock market expansion, lowering disparities in income distribution, and enhancing the effectiveness of the financial system. Sustainable economic growth, higher income level, and enhancing general social well-being are three benefits of putting these aims into practice.